Increased-specificity famine prediction using satellite observation data - Quinn, John A.; Okori, Washington; Gidudu, Anthony (First ACM Symposium on Computing for Development, 2010)
This paper examines the use of remote sensing satellite data to predict food shortages among di erent categories of house- holds in famine-prone areas. Normalized Di erence Vegeta- tion Index (NDVI) and rainfall estimate data, which can be derived from multi-spectral satellite radiometer images, has long been used to predict crop yields and hence famine. This gives an overall prediction of food insecurity in an area, though in a heterogeneous population it does not directly predict which sectors of society or households are most at risk. In this work we use information on 3094 households across Uganda collected between 2004-2005. We describe a method for clustering households in such a way that the cluster de- cision boundaries are both relevant for improved-speci city famine prediction and are easily communicated. We then give classi cation results for predicting food security status at a household level given di erent combinations of satel- lite data, demographic data, and household category indices found by our clustering method. The food security classi - cation performance of this model demonstrates the potential of this approach for making predictions of famine for speci c areas and demographic groups.